2019
DOI: 10.1371/journal.pone.0216293
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B infection among pregnant and post-partum women living with HIV and on antiretroviral therapy in Kinshasa, DR Congo: A cross-sectional study

Abstract: Background Hepatitis B virus (HBV) co-infection in HIV-infected individuals increases the risk of hepatic complications and mortality. Further, the risk of perinatal HBV transmission increases among HBV/HIV co-infected pregnant women. Although HBV is endemic in the Democratic Republic of Congo, there is little data on HBV/HIV co-infection. We aimed to assess the burden and risk factors of HBV surface antigen (HBsAg) positivity among HIV-infected pregnant and post-partum women. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…This might be because higher HIV viral load increased the susceptibility of infection by other viruses including HBV infections. The study is supported by other similar studies conducted in southeastern Ethiopia, in Jos Nigeria, and Kinshasa, the democratic republic of Congo [ 27 , 34 , 42 ]. The odds of having hepatitis B virus infection among pregnant women with CD4 less than 200, from 200–350, and 351–499 cells/mm3 was much higher than women with CD4 greater than 500 cells/mm3.…”
Section: Discussionsupporting
confidence: 87%
“…This might be because higher HIV viral load increased the susceptibility of infection by other viruses including HBV infections. The study is supported by other similar studies conducted in southeastern Ethiopia, in Jos Nigeria, and Kinshasa, the democratic republic of Congo [ 27 , 34 , 42 ]. The odds of having hepatitis B virus infection among pregnant women with CD4 less than 200, from 200–350, and 351–499 cells/mm3 was much higher than women with CD4 greater than 500 cells/mm3.…”
Section: Discussionsupporting
confidence: 87%
“…In this study the prevalence of HBV infection among pregnant women in Agena health center was 4.1%. This finding was relatively comparable with study reported from Dawuro Zone, south Ethiopia, Arba Minch Hospital, Bahir Dar city, Southwest Ethiopia and Kinshasa, Congo in which prevalence of HBV infection among pregnant women were 3.5%, 4.3%, 3.8% and 4.7% respectively [16,18,19,21].…”
Section: Prevalence Of Hepatitis B Virus In Pregnant Womensupporting
confidence: 88%
“…This seroprevalence is also lower than that found among pregnant and postpartum women living with HIV and among those undergoing antiretroviral therapy in Kinshasa (4.7%), which is in the western DRC. 4 This figure is also lower than the results pertaining to a systematic review of 28 studies ( 18studies from blood donors) that included data from 154,926 subjects. 12 However, the seroprevalence data are similar (3.3%) to the results found in national, representative dried blood spot samples that were collected during the 2013-2014 Demographic and Health Survey, which sought to determine the HBV prevalence among adults and children living in the DRC.…”
Section: Discussionmentioning
confidence: 78%
“…Although some studies that confirm the burden of viral hepatitis in the pregnant women population in several African countries are available, only very limited data are available that focus on the DRC. So far, only three studies on HBV have been identified: two conducted in urban regions 4,5 and one combining rural and urban regions. 6 The studies conducted in urban regions were performed among pregnant women living with HIV in Kinshasa or Lubumbashi, and the latter study was conducted in Kindu in the province of Maniema.…”
Section: Introductionmentioning
confidence: 99%